Benchmark review and case study of stress test for a gaming computer applied in CPU - Rezende, Tamires Martins; Medri, Alfredo Enrique Macias; Santos, Jacqueline Teixeira; Silva Junior, João Ider; Alves, Marcos Antonio; Zottino, Fabio de Carvalho (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2024: Anais do IX Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2024)
A stress test on gaming computers is one of the instruments used to ensure that machines can handle demanding memory, processing, and graphics tasks without compromising performance. This study examines benchmark tools for stress testing both personal and gaming computers, as well as degradation variables that can impact their performance. A C++ algorithm based on prime number calculation was created to stress and measure the consumption of three CPUs: AMD Ryzen 7 4800H (Nitro 5 AN515-44), 12th Gen Intel(R) Core(TM) i7-12700H (Predator Triton 300 SE), and 12th Gen Intel(R) Core(TM) i9-12900H (Predator Triton 500 SE). To provide similar conditions, the test was run with ten simultaneous threads on each machine. The results show good performance of the algorithm and revealed the superior performance of the Predator Triton 500 SE in terms of runtime. The discussion addresses the findings that can be utilized to identify potential bottlenecks and ensure a positive gaming experience.